PENINGKATAN MOTIVASI DAN HASIL BELAJAR TEMATIK MELALUI MODEL PEMBELAJARAN QUANTUM TEACHING DENGAN MEDIA POWER POINT INTERAKTIF PADA SISWA KELAS III SD NEGERI GENENG 2 MAGELANG - Uswatun Khasanah, Octavia; Ebi Praheto, Biya Ebi Praheto; Supiyah (TRIHAYU: Jurnal Pendidikan Ke-SD-an, 2022)
Class III thematic learning with the material contained in Theme 6. Energy and its Changes, Sub-theme 3. Alternative Energy at SD Negeri Geneng 2 Magelang so far still uses methods and models that are less innovative and still tend to be monotonous. This causes students to be bored, bored, and passive so that the level of motivation and thematic learning outcomes that contain the material has not been mastered optimally. The purpose of the study was to increase motivation and thematic learning outcomes through the Quantum Teaching-learning model with Interactive PowerPoint media in third-grade students of SD Negeri Geneng 2 Magelang. The research was carried out in two cycles, namely Cycle I and Cycle II, and each cycle for two meetings with thematic learning taken from class III. The results showed that the motivation and thematic learning outcomes increased which could be seen from the initial conditions, Cycle I and Cycle II. This shows that using the quantum teaching-learning model with interactive PowerPoint media can increase motivation and thematic learning outcomes in third-grade students at SD Negeri Geneng 2 Magelang.